2020
DOI: 10.22551/2020.27.0702.10168
|View full text |Cite
|
Sign up to set email alerts
|

A very rare coronary artery anomaly: Twin circumflex arteries associated with acute coronary syndrome - two cases report

Abstract: Circumflex coronary artery anomalies are the most common type so far observed. However, a dual origin of the circumflex is an extremely rare anomaly. We describe two different patients admitted to our clinic with acute coronary syndrome at the same day. Angiography revealed twin circumflex arteries: one from the left main artery and the other from the proximal right coronary artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Our case is an exceptionally rare case of a PCI of anomalous RCX in the presence of double Cx arteries; to the best of our knowledge, only three such cases have been reported previously in the literature worldwide [14,16,18]. Otlu et al reported a case of twin Cx arteries originating from the left and right coronary systems in a patient with recent-onset angina and successfully performed PCI to the diseased RCX artery using the trans-radial approach [14].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Our case is an exceptionally rare case of a PCI of anomalous RCX in the presence of double Cx arteries; to the best of our knowledge, only three such cases have been reported previously in the literature worldwide [14,16,18]. Otlu et al reported a case of twin Cx arteries originating from the left and right coronary systems in a patient with recent-onset angina and successfully performed PCI to the diseased RCX artery using the trans-radial approach [14].…”
Section: Discussionmentioning
confidence: 98%
“…Although the anomalous origin of LCX has been described to be one of the most common congenital anomalies in many large angiographic series [3][4], the occurrence of double or twin Cx coronary arteries has been reported very rarely in the literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In most of the reported cases of double Cx arteries, one Cx artery (LCX) had its origin from the left main artery while the other (RCX) had its origin from the right coronary sinus or the RCA [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. A similar finding was seen in our case with the LCX arising from the left main and the RCX arising from the ostio-proximal part of the RCA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, twin or dual circumflex arteries have also been reported originating from both the right and the left coronary artery systems, where the accessory LCX was seen originating from the right coronary artery or the right aortic sinus. [ 1 2 ] More recently, the dual origin of the circumflex artery from the main stem of the left coronary artery has also been described. Dual circumflex coronary arteries with the accessory LCX arising from the left coronary sinus [ Figures 1 and 2 ] are rare.…”
mentioning
confidence: 99%